Predictors of Hypertension among Nonpregnant Females Attending Health Promotion Clinic with Special Emphasis on Smokeless Tobacco: A Cross-Sectional Study. (16th August 2017) - Bhatt, Devika; Sharma, Shashi; Gupta, Ruchika; Sinha, Dhirendra N.; Mehrotra, Ravi
Abstract : Aim. To determine the predictors of hypertension among nonpregnant females attending a health promotion clinic. Design and Setting. A cross-sectional study was conducted during March to June 2016, at the National Institute of Cancer Prevention and Research, India. Methods. The study included 319 nonpregnant females of age 20–70 years. Demographics such as age, literacy, and income were noted. History regarding use, frequency, and quantity of smokeless tobacco was taken. Height, weight, and blood pressure were measured and body mass index was calculated. Statistical Analysis. Pearson's product-moment correlation coefficient was calculated between each of the variables of age, smokeless tobacco consumption, and body mass index versus systolic and diastolic blood pressure, respectively. The linear as well as multiple linear regression analysis was employed to identify the risk factors for hypertension. Results. A univariate linear regression analysis showed that age, smokeless tobacco consumption, and body mass index were associated with systolic blood pressure (P value < 0.001 for each). For diastolic blood pressure, high body mass index was a predictor. Multiple linear regression analysis showed that both systolic and diastolic hypertension were associated with high body mass index and low level of education. Moreover, the systolic hypertension was associated with higher age and smokeless tobacco use. Conclusion. Health promotion requires control of body mass index and smokeless tobacco cessation for preventing hypertension and its complications.